W kierunku sieci aliansów, czyli rozważania nad istotą i specyfiką multilateralnych porozumień międzyorganizacyjnych - Pietruszka-Ortyl, Anna (Towards alliance networks, i.e. considerations about the essence and specificity of multilateral interorganizational agreements, 2005)
Networks represent organizational structure which is the most convergent to the forecasted by scientists cellular model - structure of the future organization that is able to deal with specific challenges of changeable environment. Therefore the article takes into consideration the Alliance networks issues and presents their specificity and essence. Additionally the term of bilateral strategic alliance as the invariable base of constellations is shown.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 320-328